Determinants of Financial Report Quality (A Study on Banking Companies Listed on The Indonesia Stock Exchange in 2021–2023) - M. Anggi Pujakusuma; Afrizal; Muhammad Gowon (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
Quality financial statements are critical as they form the basis of decision-making for investors, regulators, and other stakeholders. This study seeks to provide empirical evidence on how various factors including “Leverage, Profitability, Institutional Ownership, Managerial Ownership, Independent Board of Commissioners, Audit Committee, Female Executives, and Competence” affect the quality of financial statements in banking companies listed on the IDX. The main focus of the study is to review the collective and individual impact of these variables. The secondary data source of this research is the annual report and performance summary of banking companies for the 2021-2023 period which are accessed through the IDX portal and the company's official website. Of the 47 eligible companies, this study took a sample of 27 banking companies through purposive sampling technique. The research hypothesis was then tested by applying multiple regression analysis. The results of this study reveal that Leverage, Institutional Ownership, Independent Board of Commissioners, and Audit Committee have a significant influence on the quality of financial statements. However, Profitability, Managerial Ownership, Female Executives, and Competence did not show a similar impact. Interestingly, when reviewed together, all these factors collectively affect financial statement quality. These findings underscore the important role of corporate governance in driving financial statement quality, while suggesting that some elements such as female executives and managerial ownership may not have a direct impact. Future research could explore additional variables or different sectors to deepen the understanding of financial reporting quality.